Analisis Dampak Penggunaan Aplikasi Quizizz pada Hasil Belajar Materi Kebutuhan dan Keinginan Kelas 4 SDN 7 Kampungdalem - Della Hana Tista; Ria Fajrin Rizqy Ana (Universitas Nusantara PGRI Kediri, 2024)
This research aims to examine the impact of using the Quizizz application on learning outcomes to make the learning process more interactive and innovative. The research uses a qualitative approach with a descriptive type of approach. The subjects of this research are 1 teacher and 18 fourth-grade students at SDN 7 Kampungdalem. Research instruments use observation guidelines, test questions, and documentation. The data analysis used includes data reduction, data presentation, and conclusion drawing. The results of this study indicate that the Quizizz application as a learning media for IPAS lessons on needs and wants for 4th grade at SDN 7 Kampungdalem falls into the very good category. This is evidenced by the implementation of the Quizizz application, which ran according to the instrument validation with a score of 90% on the Likert scale, while the students' learning outcomes received a score of 96%. This application provides satisfaction to its users, including teachers and students.